Acute mesenteric ischemia in an African American patient with heterozygous factor V Leiden deficiency - Hadiatou Barry; Ali Ghani; David Gary Smith (Greater Baltimore Medical Center, 2019)
It is well documented that factor V Leiden mutation (FVL) is a common hypercoagulable risk factor in the Caucasian population. Patients with homozygous FVL mutation have an increased risk for venous thromboembolism. However, there have been few cases of heterozygous FVL mutation associated with arterial thrombosis described in the literature. Our case report presents an African American (AA) female with heterozygous FVL mutation who presented with acute arterial mesenteric ischemia.